Uso de Análisis de Covarianza (ANCOVA) en investigación científica (Use of covariance analysis (ANCOVA) in scientific research) - Badii Zabeh, Mohammad Hosein; Castillo, J.; Wong, A. (Facultad de Contaduría Pública y Administración U.A.N.L., 2008)
Abstract. The basics of the ANalisis of COVAriance (ANCOVA) are given. The objectives and the application of ANCOVA are laid out. Techniques for the estimation of contrasts and for the control and reduction of the degree of error are discussed. The application of a simple ANCOVA using real data is highlighted. The application of this technique in fixing the auxiliary variable in experimentation is emphasized. Resumen. Se presentan las bases del ANálisis de COVArianza (ANCOVA). Se manejan los propósitos y la aplicación de este método estadístico. Se discuten las técnicas para la estimación de los contrastes, el control y la disminución del grado de error. Se presentan un ANCOVA simple mediante un ejemplo de datos reales. Se enfatiza el papel de esta técnica estadística en fijar el efecto de la variable auxiliar en el experimento.